Uma análise da influência do orçamento participativo na gestão pública do município de Araraquara/SP - Ventura, Ivanise Aurora (2020)
The present work had as objective to analyze the management of the Participatory Budget by the Municipality of Araraquara, interior of the state of São Paulo, having as a directive hypothesis that, throughout this period, the process of Participatory Budget through its systematic and criteria of popular participation, has contributed to the exercise of citizenship and achieved its objectives of economic redistribution, through popular demands. To carry out the work, bibliographical surveys of the theme addressed for the research were carried out. The empirical analysis consisted of consultations on the minutes of the meetings of the sub-regional, regional and thematic plenary sessions; analysis of secondary data, in addition to consultation with the internal regulations of the OP of the management analyzed. Other resources used for the research were the observation in loco of the regular sub-regional, regional and thematic meetings of the year 2019, in addition to interviews with those involved in the OP, representatives of the participating population and technicians from the city of Araraquara. The experience discussed showed that, in fact, the population in Araraquara has participated, and the investments defined by the population are respected by the executive. However, the budget forecast for the works and projects of the OP has created doubts among the COP's advisers, showing that the administration should expand the debate on the public budget with those involved.